Women in the Military Sphere: Some Issues of Social Adaptationilitary Sphere - Gevorgyan, Mariam (Journal of Sociology: Bulletin of Yerevan University, 2020)
Since the 1970s, feminist movements and the recognition of gender equality as one of the basic human rights, as well as a number of other legal, socio-political changes in the armed forces have recorded significant structural changes that have provided the “weaker sex” with wider access to this area. The article deals with issues related to the dynamic processes of social integration of women in the army environment. Based on the analysis of a number of models of their involvement in the armed forces, the main factors influencing the stage-by-stage processes of such involvement in this specific area are presented.